Solve your doubts and expand your knowledge with IDNLearn.com's extensive Q&A database. Our community is here to provide the comprehensive and accurate answers you need to make informed decisions.
[tex]\\ \rm\Rrightarrow \dfrac{6}{x^2-3x}=\dfrac{12}{x}+\dfrac{1}{x-3}[/tex]
[tex]\\ \rm\Rrightarrow \dfrac{6}{x(x-3)}=\dfrac{12}{x}+\dfrac{1}{x-3}[/tex]
[tex]\\ \rm\Rrightarrow \dfrac{6}{x(x-3)}=\dfrac{12(x-3)+x}{x(x-3)}[/tex]
[tex]\\ \rm\Rrightarrow 6=12x-36+x[/tex]
[tex]\\ \rm\Rrightarrow 6=13x-36[/tex]
[tex]\\ \rm\Rrightarrow 13x=42[/tex]
[tex]\\ \rm\Rrightarrow x=\dfrac{42}{13}[/tex]